Case Series: Hypercalcemia From Granulomatous Silicosis Developing After COVID-19 Infection. (October 2021) - Bray, Ashley; Reyes, Jonathan Vincent M.; Tarlin, Nancy; Stern, Aaron
Hypercalcemia is one of the most commonly encountered laboratory abnormalities in clinical medicine. Various causes have been well established. However, it is likely that the novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), may be a newly found cause of this frequent finding, especially amongst those with a history of cosmetic surgery, specifically by means of silicone injection. In this case series, we describe 2 patients presenting with symptomatic hypercalcemia likely from their prior silicone injections. Interestingly, each patient only developed symptoms of hypercalcemia following infection with SARS-CoV-2.